2020
DOI: 10.1111/tpj.14810
|View full text |Cite
|
Sign up to set email alerts
|

Ptr1 evolved convergently with RPS2 and Mr5 to mediate recognition of AvrRpt2 in diverse solanaceous species

Abstract: Summary The Ptr1 (Pseudomonas tomato race 1) locus in Solanum lycopersicoides confers resistance to strains of Pseudomonas syringae pv. tomato expressing AvrRpt2 and Ralstonia pseudosolanacearum expressing RipBN. Here we describe the identification and phylogenetic analysis of the Ptr1 gene. A single recombinant among 585 F2 plants segregating for the Ptr1 locus was discovered that narrowed the Ptr1 candidates to eight nucleotide‐binding leucine‐rich repeat protein (NLR)‐encoding genes. From analysis of the ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 74 publications
(105 reference statements)
2
46
0
1
Order By: Relevance
“…First, we tested pPPED by agroinfiltration of N. benthamiana leaves ( Figure 2A ). The target was a mutated allele of the avrRpt2 gene of the bacterial plant pathogen Pseudomonas syringae ( avrRpt2[C122A] ; (Mazo-Molina et al, 2020 ), delivered on t-DNA by a co-infiltrated Agrobacterium strain. The AvrRpt2 protein elicits programmed cell death in N. benthamiana , and the C122A mutation abolishes this activity.…”
Section: Resultsmentioning
confidence: 99%
“…First, we tested pPPED by agroinfiltration of N. benthamiana leaves ( Figure 2A ). The target was a mutated allele of the avrRpt2 gene of the bacterial plant pathogen Pseudomonas syringae ( avrRpt2[C122A] ; (Mazo-Molina et al, 2020 ), delivered on t-DNA by a co-infiltrated Agrobacterium strain. The AvrRpt2 protein elicits programmed cell death in N. benthamiana , and the C122A mutation abolishes this activity.…”
Section: Resultsmentioning
confidence: 99%
“…Nanopore sequences were generated for the SP accession LA1589 using the method described in Mazo-Molina et al 45 and used for validation of SV genotyping. Briefly, Nanopore libraries were constructed from the HMW DNA of LA1589 using the Ligation Sequencing Kit (SQK-LSK109) and sequenced on the MinION R9 flow cells for 48 h. Basecalling was performed using Guppy (v3.1.5).…”
Section: Methodsmentioning
confidence: 99%
“…Six effectors (Minc3s00127g05433, scaf-fold166774_cov71.g22242, Minc3s00081g03887, Minc3s00642g15511, Minc3s01334g22880, and Minc3s07235g40885) were obtained from M. incognita (Figure 1A). Previous research reported that the molecular weight of effectors that can trigger plant immunity is generally smaller than the disease-resistance protein [50,51]. The molecular weight of the effector Minc3s07235g40885 obtained via IP and LC-MS is 179.48KD (Figure 1A), which is bigger than PsoRPM3 (107.490 KD).…”
Section: Five Candidate Effectors: Gene Amplification and Sequence Analysismentioning
confidence: 82%